Kejadian Hujan Asam di Kabupaten Bogor dan Retensi Timbal pada Domba Lokal yang Diberi Ransum Berkadar Timbal Tinggi - D Diapari; H. M H Bintoro; J Jachja; K A Notodiputro; M S Saeni (Media Peternakan, 2008)
The objectives of this research were: 1) to find out whether acid rain has taken place in Bogor Regency area and its effect on the lead (Pb) content in soil and roughage in the region, 2) to predict the correlation of Pb content in rain water and soil, and the content of Pb in roughage in the Bogor regency area, 3) to study the impact of acid and Pb content in the ration to sheep daily gain and measure Pb content in liver, kidney and meat. The results showed that in Bogor regency area the acid rain occurred during the dry season but not in the wet season. The Pb content in the rainwater and soil were not affected by acid rain. There was no correlation of Pb content between soil and roughage. Acid containing ration decreased daily gain, but not for the ration of high Pb-content. Acid containing ration increased Pb content in the kidney but not in the liver and meat. However, high Pb content in the ration increased the Pb content in the liver and kidney but not in the meat. Key words: acid rain, Pb, Bogor, local sheep